Investigating Students’ ESP Target and Learning Needs: A Case Study at Tourism and Industry Program - Heriyanti; Suharto, Muhammad Fiqri; Yuliana; Wafom, Yunike (Universitas Cokroaminoto Palopo, 2024)
English for Specific Purpose (ESP) is essential for vocational schools presently. However, many vocational schools still provided general English language material under the students' specific program. This study investigated the target and learning needs of the travel and tourism industry program students of SMK Negeri 1 Kota Sorong in learning English. Thirty-five students participated in this study. Data were obtained from Open-ended Questionnaires and semi-structured interviews. The study revealed that the students' targets in learning English were to communicate in English fluently both in spoken and written, be successful in the workplace and higher education, and have an advanced English proficiency level to be a guide in a travel and tourism agency. The students' learning needs were the learning English inputs spoken and written with pictures, learning English with the short texts with a specific topic related to the program, various activities to become active and independent learners. However, they still wanted the teacher to read the text and translate it directly with them. Therefore, students expected the school to design an ESP program to make the English learning process specifically appropriate for the travel and tourism industry program.